Psychometric Properties of Career Decision-Making Difficulties Questionnaire: Lithuanian Version - Vadvilavičius, Tadas; Burčikaitė, Donata; Jakštaitytė, Karolina; Petrulis, Tadas (Psichologija, 2024)
Valid and reliable methods are needed to assess the difficulties young people often face in making career-related decisions. A cross-sectional study was conducted to test the psychometric characteristics (internal consistency, discriminant, convergent and structural validities) of the Lithuanian version of the Career decision-making difficulties questionnaire (Gati et al., 1996) in a sample of Lithuanian students (N = 255). The results revealed that the Lithuanian version of Career decision-making difficulties has good internal consistency. Adequate convergent validity was confirmed by finding statistically significant positive relationships with indecisiveness, and discriminant validity was confirmed by finding statistically significant negative relationships with career self-efficacy. Finally, structural validity was confirmed by confirmatory factor analysis, which revealed that a 10-factor structure was the most appropriate. The results of the research showed that the Lithuanian version of the Career decision-making difficulties questionnaire is a suitable measurement tool, but further studies on the evaluation of the scale are needed.
Keywords: career decision-making difficulties; indecisiveness; career self-efficacy; validity; psychometric properties